BS ISO 23678-1. Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats (including free-fall lifeboats) and rescue boats (including fast rescue boats), launching appliances and release gear. Part 1. General requirements for training providers (25th August 2021) - British Standards Institution,
No abstract available